Multiple independent transpositions of mitochondrial DNA control region sequences to the nucleus - Sorenson, Michael D. (The National Academy of Sciences of the USA, 1996)
Transpositions of mtDNA sequences to the nuclear genome have been documented in a wide variety of individual taxa, but little is known about their taxonomic frequency or patterns of variation. We provide evidence of nuclear sequences homologous to the mtDNA control region in seven species of diving ducks (tribe Aythyini). Phylogenetic analysis places each nuclear sequence as a close relative of the mtDNA haplotypes of the specie(s) in which it occurs, indicating that they derive from six independent transposition events, all occurring within the last ≈1.5 million years. Relative-rate tests and comparison of intraspecific variation in nuclear and mtDNA sequences confirm the expectation of a greatly reduced rate of evolution in the nuclear copies. By representing mtDNA haplotypes from ancestral populations, nuclear insertions may be valuable in some phylogenetic analyses, but they also confound the accurate determination of mtDNA sequences. In particular, our data suggest that the presumably nonfunctional but more slowly evolving nuclear sequences often will not be identifiable by changes incompatible with function and may be preferentially amplified by PCR primers based on mtDNA sequences from related taxa.